2016
DOI: 10.3354/cr01354
|View full text |Cite
|
Sign up to set email alerts
|

La Niña events before and after 1979 and their impact in southeastern South America during austral summer: role of the Indian Ocean

Abstract: In this study, we analyzed the influence of interannual variability in sea surface temperature (SST) on the climate of southeastern South America (SESA) during austral summer. We found that the correlation between the El Niño Southern Oscillation (ENSO) and rainfall over southern Brazil-northern Uruguay (SB-NU) was not statistically significant between 1949 and 1978, but it was significant between 1979 and 2009. The results show that this change in correlation was largely due to the modified rainfall response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Besides influencing precipitation over SESA, these tropical oceans interact with each other, inducing SST anomalies in remote basins through atmospheric and oceanic teleconnections. Cazes‐Boezio and Talento (2016) analysed La Niña events that occurred before and after 1979 and identified significant differences in SST fields in regions adjacent to the central equatorial Pacific. Their results show that events that occurred after 1979 were accompanied by high temperatures in the Atlantic and Indian Oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Besides influencing precipitation over SESA, these tropical oceans interact with each other, inducing SST anomalies in remote basins through atmospheric and oceanic teleconnections. Cazes‐Boezio and Talento (2016) analysed La Niña events that occurred before and after 1979 and identified significant differences in SST fields in regions adjacent to the central equatorial Pacific. Their results show that events that occurred after 1979 were accompanied by high temperatures in the Atlantic and Indian Oceans.…”
Section: Introductionmentioning
confidence: 99%
“…(2009) show that rainfall correlation with ENSO was not significant until 1977. Cazes‐Boezio and Talento (2016) identified a similar change for summertime rainfall over SESA: the correlation between the Niño3.4 index and rainfall resulted significant for 1979–2009 but not for 1949–1978, and they associate this change to a different behaviour of the Indian Ocean during La Niña events.…”
Section: Introductionmentioning
confidence: 84%
“…Scatterplots were constructed between rainfall in ZN/ZS and Niño3.4 index for subperiods P1 and P2, indicating ENSO events. Warm (El Niño) and cold (La Niña) ENSO events are defined based on Cazes‐Boezio and Talento (2016), that is, we consider El Niño (La Niña) years if the Niño3.4 index is larger (smaller) than 0.7°C (−0.7°C) and neutral years the ones with Niño3.4 values between −0.7 and 0.7°C.…”
Section: Methodsmentioning
confidence: 99%
“…Their results provided evidence that the variability of the Indian Ocean SST can modulate the precipitation in SA during the austral autumn through remote mechanisms. In another study, Cazes‐Boezio and Talento (2016) analysed the teleconnections associated with ENSO before and after 1980. They concluded that after 1979 the events were accompanied by high temperatures in the Atlantic and Indian Oceans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, similarly to ENSO, recent studies highlight the role of the Indian Ocean in the climate of SA (Cazes-Boezio & Talento, 2016;de Souza et al, 2021;Kayano et al, 2021aKayano et al, , 2021bKayano et al, , 2021cTaschetto & Ambrizzi, 2012). Taschetto and Ambrizzi (2012) investigated the atmospheric response to the tropical Indian Ocean basin warming and its impact on the precipitation in SA when it was associated with or independent of ENSO.…”
Section: Introductionmentioning
confidence: 99%